Optimasi Multirespon Purwarupa Electrical Discharge Machine (EDM) Menggunakan Metode Taguchi-Grey Relational Analysis - Angga Sateria; Eko Yudo; Zulfitriyanto Zulfitriyanto (Manutech : Jurnal Teknologi Manufaktur, 2019)
EDM is one of the nonconventional machining processes when making workpieces with conventional machining processes is difficult. This process has been used effectively in machining hard, high-strength and high temperature materials such as high speed steel (HSS) materials. In this study, prototype of EDM machines was carried out with engine variables such as current (A), pulse on time (µs) and pulse off time (µs). The material used is high speed steel (HSS) material used in cutting tools such as turning tools and milling tools. Surface roughness and material removal rate are responses observed to determine the quality of material remaval. The quality characteristic of the surface roughness response is "smaller is better" and the quality characteristics of the material removal rate response is "larger is better. The purpose of this study is to determine the best process parameter level to achieve the required performance characteristics in the material removal process using prototype EDM machines using the gray relational analysis (GRA) method, three process parameters are selected such as current, pulse on time, and pulse off time. The taguchi 3 x 3 x 3 design is used as an experimental design.The best parameter level obtained is current 40 ampere, pulse on time 200 µs, pulse off time 20 µs.